Yixintongmai Inhibits Proliferation and Migration and Promotes Apoptosis of Vascular Smooth Muscle Cells Cultured with High Glucose. (4th May 2021) - Guo, Jingjing; Zhao, Di; Dong, Pingshuan
Abstract : Objective . This study was designed to evaluate the effects of yixintongmai on proliferation, migration, and apoptosis of vascular smooth muscle cells (VSMCs) cultured with high glucose. Methods . VSMCs of the thoracic aorta from 5- to 8-week-old male Sprague-Dawley rats were cultured with normal (4.5 mM) or high (25 mM) glucose, respectively. The concentration of yixintongmai powder at 360  μ g/ml was chosen according to pre-experimental results. Results . Yixintongmai inhibited the proliferation of VSMCs (CCK-8 assay: 0.75 ± 0.04 versus 0.98 ± 0.09 OD, P < 0.001 ; cell counting: 37533 ± 1861 versus 56009 ± 3779 cells/well, P < 0.001 ) and the expression of proliferating cell nuclear antigen (0.74 ± 0.08 fold, P < 0.001 ) as compared with high glucose (HG). Yixintongmai inhibited the migration of VSMCs (transwell assay: 146 ± 16 versus 265 ± 62 cells; P < 0.001 ), scratch wound assay (0.17 ± 0.01 fold, P < 0.001 ), and the expression of matrix metalloproteinases-9 (0.87 ± 0.03 fold, P < 0.001 ) as compared with HG. Yixintongmai decreased mitochondrial membrane potentials (0.36 ± 0.12 fold, P < 0.001 ) and promoted early (2.11 ± 0.20 fold, P < 0.01 ) and late (2.11 ± 0.28 fold, P < 0.01 ) apoptosis of VSMCs as compared with HG. Yixintongmai inhibited the expression of B-cell lymphoma 2 (0.83 ± 0.07 fold, P < 0.01 ) and stimulated the activity of cleaved-capase-3/caspase-3 (2.00 ± 0.12 fold, P < 0.05 ) as compared with HG. Yixintongmai inhibited reactive oxygen species generation (0.46 ± 0.03 fold, P < 0.01 ) and the expression of NADPH oxidase-1 (0.84 ± 0.04 fold, P < 0.001 ), nuclear factor-kappa B (NF- κ B) p65 (0.71 ± 0.07 fold, P < 0.001 ), phosphorylated NF- κ B p65 (0.39 ± 0.02 fold, P  < 0.0001), and inhibited nuclear translocation of NF- κ B p65 (0.87 ± 0.03 fold, P < 0.001 ) in VSMCs as compared with HG. Conclusions . Yixintongmai inhibits the proliferation and migration and promotes the apoptosis of VSMCs cultured with HG, which suggests the potential anti-atherosclerotic effects of this traditional Chinese medicine.